2017
DOI: 10.1071/py16053
|View full text |Cite
|
Sign up to set email alerts
|

‘It depends on the consultation’: revisiting use of family members as interpreters for general practice consultations – when and why?

Abstract: Family members continue to be used as interpreters in medical consultations despite the well-known risks. This paper examines participant perceptions of this practice in three New Zealand clinics chosen for their frequent use of interpreters and their skill in using them. It is based on a detailed study of 17 video-recorded interpreted consultations and 48 post-consultation interviews with participants (5 doctors, 16 patients and 12 interpreters, including 6 family members). All participants expressed satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…13 Several family members may be present during consent, interested in the type of questions which will be asked. However, relying on family members to translate is problematic and labour intensive 14…”
Section: ) Consent and Assessmentsmentioning
confidence: 99%
“…13 Several family members may be present during consent, interested in the type of questions which will be asked. However, relying on family members to translate is problematic and labour intensive 14…”
Section: ) Consent and Assessmentsmentioning
confidence: 99%
“…There is also evidence patients and family members may be satisfied with or even prefer family member interpreters [32].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Based on these factors, migrant parents will often ask their own children to interpret for them (6). A study by Hilder et al (8)found that most people are satisfied with using family members as interpreters because of the trust and personal relationship they have with family.…”
Section: Introductionmentioning
confidence: 99%